Pengaruh Operation Management Dan Cash To Cash Cycle Terhadap Financial Performance - Margarita Ekadjaja; Rorlen (Jurnal Ekonomi, 2022)
During the Covid 19 pandemic companies must pay attention to the cash to cash cycle in order to survive and develop by continuing to innovate and improve company performance. The aim of this research is to determine the effect of operation management and the cash to cash cycle on company financial performance. The research subjects are manufacturing companies listed on the Indonesia Stock Exchange in 2018 to 2020. The dependent variable in this research is financial performance and the independent variable is operation management which is proxied by inventory control and TQM, and the cash to cash cycle variable which is proxied by the average collection period and average payment period. The test analysis uses multiple linear methods and the test results show the results of data analysis using double linear regression analysis. It can be concluded that only the average payment period variable has no effect on financial performance while the inventory control, TQM and average collection period variables have a significant positive effect on financial performance.